UTANG KONSUMTIF RUMAH TANGGA DALAM PERSPEKTIF KONVENSIONAL DAN SYARIAH - HERISPON HERISPON (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". It can be observed the phenomenon of socio-economic life in the neighboring order, if one household can buy an item, then other households can be aroused to buy the same goods without having to think about the function and usefulness of the products they buy. This kind of action is called a hard-to-follow behavior with the phrase "if people can buy, why do not we," even with debt, this condition requires households to make their choice of consumption. Also the development of technology and information is exploited by certain institutions, such as banking, or non banking to introduce their products through the media visual media, print media, radio media, internet media and others, which can stimulate, generate interest, desire, and intention to behave the ladder becomes a real behavior to have a product through the path of debt.